AN INSTRUCTION BASED ON SOCIAL COGNITIVE LEARNING THEORY AND METACOGNITION APPROACH TO IMPROVE SELF-AWARENESS AND SOCIAL SKILLS FOR UNDERGRADUATE STUDENTS - Mou Haiyan; Watcharee Sangboonraung; Nirat Jantharajit (Journal of Educational Review Faculty of Education in MCU, 2025)
The purpose of this study was: 1) To compare self-awareness of Bachelor degree students between before and after learned based on social cognitive learning theory and metacognition approach. 2) To compare social skills of Bachelor degree students between before and after learned based on social cognitive learning theory and metacognition approach. The research samples were 30 bachelor students of China college in the academic year 2023. The research instruments consisted of 1) Instructional plans 2) The assessment form for self-awareness, 3) The assessment form for social skills of students. 4) Descriptive statistics and t-test for Dependent samples. The research results revealed as follows: 1) The students learned based on social cognitive learning theory and metacognition approach had higher of self-awareness at after learning than before learning, at the .05 level of significance. 2) The students learned based on social cognitive learning theory and metacognition approach had higher of social skills at after learning than before learning at the .05 level of significance.